The Criminal Responsibility of Perpetrators Who Intentionally Persuade Children to Commit Incest (A Study of Decision Number: 56/Pid.Sus/2024/PN Tjk) - Akbar As, Muhammad Zahien; Prasetyawati, S. Endang; Aprinisa, Aprinisa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Data on sexual violence cases in Indonesia has increased in recent years. Based on various reports in 2021, the National Commission on Violence Against Women recorded a spike in sexual violence during the COVID-19 pandemic. In that year, there were more than 8,234 cases, in 2022 it increased with around 4,371 reports of sexual violence and in 2023 there were 4,150 cases of violence. Sexual violence in Indonesia is regulated in Law Number 17 of 2016 concerning the Establishment of Government Regulations in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection. This article analyzes the criminal responsibility for perpetrators who deliberately induce children to have sexual intercourse and analyzes the factors that influence the perpetrator in committing this criminal act. Based on research results, the factors that influence the perpetrator are external and internal factors which encourage the perpetrator to commit the crime by deliberately persuading the child to have sexual intercourse. Based on this, in the trial the panel of judges stated that the perpetrator had been legally and convincingly proven guilty of committing a criminal act and was sentenced to imprisonment for 1 (one) year at LPKA Class II Bandar Lampung in Masgar Pesawaran and Job Training for 6 (six) months at LPKS (Social Welfare Development Institute)Key words: sexual intercourse, criminal act, criminal liability.